Recent developments in myelofibrosis - Mesa RA (Dove Medical Press, 2012)
Raoul Tibes, James M Bogenberger, Ruben A MesaDivision of Hematology and Oncology, Mayo Clinic, Scottsdale, AZ, USAAbstract: The myeloproliferative neoplasm of myelofibrosis (MF) is clinically constituted by individuals both with primary MF, as well as those that evolved from an antecedent polycythemia vera or essential thrombocythemia. Individuals presenting with MF have a heterogeneous phenotype which can involve significant constitutional symptoms (night sweats, fevers, weight loss, fatigue, variable but frequently problematic splenomegaly, and multifactorial cytopenias). These individuals clearly have decreased survival. Refinement of MF prognostic scores can distinguish from survival as poor as 16 months, to a median survival of 185 months. Sadly, although curative, allogeneic stem cell transplant still has sobering success rates for individuals of the standard ages for MF. Recent reports suggest less than half of patients will be alive at 3 years after allotransplant above the age of 60 years. The most important recent advancement in MF therapy has been the development of Janus kinase 2 (JAK2) inhibitors led by ruxolitinib, now Food and Drug Administration approved in the United States, and several other JAK2 inhibitors (in testing) including SAR302503, CYT387, and SB1518. In randomized, placebo-controlled studies, ruxolitinib was demonstrated to be superior for the improvement of splenomegaly and symptoms. These benefits are mirrored across other JAK2 inhibitors. Improving anemia remains an unmet need in MF and is currently being evaluated by clinical trials utilizing the JAK2 inhibitor CYT387, as well as pomalidomide. Additional areas of interest for MF therapy include the inhibition of histone/lysine deacetylases, hedgehog pathway inhibition, as well as combination strategies with JAK2 inhibitors.Keywords: myeloproliferative neoplasm, myelofibrosis, JAK2 inhibitors